1967
DOI: 10.1042/bj1040306
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of triglyceride fatty acid by the perfused rat heart

Abstract: 1. Chyle lipids, labelled with (14)C, are taken up and oxidized by the isolated perfused rat heart. 2. In recirculatory perfusions, when chyle lipids are the sole exogenous energy source, about 24% of the total oxygen uptake is accounted for by their oxidation. This proportion is not changed by starvation of the rats for 48hr. and falls when an external work load is imposed on the left ventricle. 3. With albumin in the perfusion medium, the rate of (14)CO(2) output is reduced by half and there is a rise in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

1968
1968
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…Significant cardiac utilisation of d<1.006 lipoprotein-TAG (CM) was also found in isolated rat heart [9] TAG oxidation accounted for 40% of CO 2 production (equivalent to that of NEFA oxidation) [10] (and in broad agreement with earlier studies [11]). Further evidence for a role for…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…Significant cardiac utilisation of d<1.006 lipoprotein-TAG (CM) was also found in isolated rat heart [9] TAG oxidation accounted for 40% of CO 2 production (equivalent to that of NEFA oxidation) [10] (and in broad agreement with earlier studies [11]). Further evidence for a role for…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…This loss was a result of release of the enzyme in perfusion medium. Such a release of lipoprotein lipase in the perfusion medium after heparin perfusion of the heart has been reported by Enser et al (1967) (Table 4) and may be analogous to the hepatic triacylglycerol lipase. It is known that hepatic triacylglycerol lipase is not inhibited by NaCl and also hydrolyses the triacylglycerol-rich lipoproteins, although less efficiently Augustin et al, 1976).…”
Section: Discussionmentioning
confidence: 73%
“…Studies performed in vivo (Eisenberg & Levy, 1975), in isolated perfused hearts (Delcher et al, 1965;Enser et al, 1967; Fielding & Higgins, 1974;Higgins & Fielding, 1975) and in vitro (Eisenberg & Rachmilewitz, 1975) have all implicated an involvement of lipoprotein lipase (EC 3.1.1.3) in the hydrolysis of the triacylglycerolrich plasma lipoproteins. It has been suggested that this hydrolysis may occur at a site close to the endothelial cells lining the blood capillaries (Robinson, 1963;Blanchette-Mackie & Scow, 1971), where the lipoprotein lipase involved is believed to be located .…”
mentioning
confidence: 99%
“…[14C]palmitic acid measured in the experiments of Evans et al (1963) and considerably in excess of the rates of uptake and oxidation of chylomicron fatty acid by the isolated saline-perfused rat heart (Crass & Meng, 1966;Kreisberg, 1966;Scheur & Olson, 1967;Enser et al 1967). Thus chylomicron fatty acids could be potentially as important in the energy metabolism of the heart as unesterified fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abnormal capillary permeability in such saline-perfused hearts discussed above casts some doubt on the true physiological significance of the results in relation to the initial removal of chylomicrons from the circulation in vivo. Moreover, these preparations do not tolerate well higher perfusate concentrations of chylomicrons which still fall within the physiological range (Enser et al 1967). …”
Section: Discussionmentioning
confidence: 99%